Multiparasitism of stink bug eggs: competitive interactions between Ooencyrtus pityocampae and Trissolcus agriope - Mohammadpour, Marzie; Jalali, M. Amin; Michaud, J. P.; Ziaaddini, Mahdi; Hashemirad, Hamid (My University, 2014)
Females of Trissolcus agriope (Platygastridae) avoid host (Brachynema signatum) eggs parasitized by conspecifics or Ooencyrtus pityocampae (Encyrtidae), but females of the latter species will superparasitize and multiparasitize, although they mostly attack unparasitized eggs. Females of T. agriope were more efficient in the laboratory and parasitized more hosts in 24 and 48 h. In multiparasitized hosts, O. pityocampae was a superior larval competitor and could complete also development as a facultative hyperparasitoid. When females of both species foraged together, T. agriope parasitized significantly more than O. pityocampae, about 50%in both cases, although O. pityocampae almost doubled its parasitism rate as the exposure period was lengthened from 24 h to 48 h. When O. pityocampae followed T. agriope in sequential foraging bouts, the former species successfully parasitized more hosts than the latter. The advisability of co-releases of both species to improve biological control of first generation B. signatum in Iranian pistachio orchards is discussed.

Citation: Mohammadpour, M., Jalali, M. A., Michaud, J. P., Ziaaddini, M., & Hashemirad, H. (2014). Multiparasitism of stink bug eggs: Competitive interactions between Ooencyrtus pityocampae and Trissolcus agriope. Retrieved from http://krex.ksu.edu
Keywords: Biological control; Brachynema signatum; Interspecific competition; Intraguild interactions; Encyrtidae; Scelionidae